Kajian food waste untuk meningkatkan ekonomi keluarga - Khusniyah, Khusniyah; Muis, Zeni Zainal; Kumalasari, Dwi Apriyanti (Jurnal Agrotek Ummat, 2022)
Indonesia is the second largest contributor to food waste in the world. The Global Hunger Index said that the level of hunger in Indonesia is at a serious level but processing food waste can have a positive impact on the family economy. This study first aims to determine the factors that influence the behavior of preparing food, secondly to determine the factors that influence the behavior of wasting food, and thirdly to find out that food waste can improve the family's economy. This type of qualitative descriptive research was carried out in Jiken Village, Tulangan District, Sidoarjo Regency, East Java purposively using primary and secondary data. Data were taken by sampling with household interviews and analyzed to obtain answers to the research objectives. The results showed that the behavioral factors of the household preparing food include the number of family members, planning to prepare food, the amount of food preparation costs, the intensity of cooking a day, and whether or not they have ever learned to cook. Factors that influence household behavior in disposing of food include inappropriate menus, number of menus, schedule of eating more than twice a day, appearance of ordinary food, and inappropriate taste of food. Food waste can improve the family's economy, namely 60% food waste can be used to animal feed. It is hoped that this research method will produce patterns of household behavior in preparing food and reducing the amount of food waste and the family economy will increase from food waste processing.